New Data on the Mineral and Geochemical Composition of Bottom Sediments in the Tanatar Soda Lakes (Kulunda Plain, Russia) - Ovdina Ekaterina; Strakhovenko Vera; Malov Georgy; Malov Viktor; Solotchina Emilia (Russian Journal of Earth Sciences)
The lakes of the Kulunda plain have long attracted the attention of researchers. A detailed 10 geochemical testing of a chain of four small soda lakes of the Tanatar group allowed answering a 11 number of questions. We used a complex of modern methods of mineralogy and geochemistry to 12 update and add new data on the main phases of bottom sediments. The studied lakes have a pH ≥ 8 13 and a TDS of 2.1–41.5 g/L and a soda water composition. It has been established that over the 14 past ∼ 100 years there has been no change in the mineral composition of bottom sediments. The 15 main phases of the bottom sediments consist of intermediate and high – Mg calcite and Ca-excess 16 dolomite. Magnesite is presented only as a small impurity. The formation and accumulation of these 17 minerals occur throughout the core of bottom sediments. According to received data, a change in the 18 hydrological regime of the catchment area was established. The feeding regime of the lakes has been 19 changed because of the drying up of the Rublevaya River.